Iowa Birdline update, November 15, 1993 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1993)
Email of the Iowa Birdline update for November 15, 1993. Highlights include the sighting of a Mew Gull; a Thayer's Gull has been sighted at the same location. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed